IMPLEMENTASI PELAKSANAAN PROGRAM KAMPUS MENGAJAR ANGKATAN 1 TERDAMPAK PANDEMI COVID-19 - Tengku Muhamad Fajar Anugrah (GoAcademica Research dan Publishing, 2021)
The purpose of implementing the Teaching Campus program is to provide opportunities for students to develop themselves through activities and creativity outside the scope of lectures. The Teaching Campus Program has the aim that students can be directly in the field with various conditions in elementary schools throughout Indonesia. The research method used is a qualitative approach. The subject of this research is SDS ABC North Jakarta, totaling 12 students. The object of the research is the implementation of the teaching campus at SDS ABC, North Jakarta. Data was collected by using observation and documentation techniques. From the results of observations, it can be concluded. The first program implemented was training on adaptation of online learning technology to SDS ABC North Jakarta students that went well, and Assisted School Administration and Teachers. The SDS ABC learning process method used online and offline learning methods. The learning media used are lesson plans distributed in WhatsApp groups and theme books (textbooks). The use of video conferencing applications such as Zoom or Gmeet, is only done once every two weeks or once a month. offline learning is done once a week.